Modifiye stoppa yaklaşımıyla cerrahi tedavi edilen asetabulum kırıklarının fonksiyonel ve radyolojik sonuçları / Functional and radiological outcomes of acetabulum fractures operated by using the modified stoppa approach - HUZEYFE ÇETİN, AHMET (My University, 2021)
Amaç: Kliniğimizde Modifiye Stoppa yaklaşımı ile opere edilen asetabulum kırıklarının fonksiyonel ve radyolojik sonuçlarını değerlendirmektir. Gereç ve Yöntem: 2012-2020 yılları arasında asetabulum kırığı nedeniyle kliniğimize başvurup, Modifiye Stoppa yaklaşımıyla cerrahi tedavisi gerçekleştirilen ve en az 1 yıl takibi olan 40 hasta bu çalışmaya dâhil edildi. Kayıtlar, yaş, cinsiyet, travma oluşum şekli, kırık tipi, eşlik eden yaralanma, ameliyata kadar geçen süre, ameliyat süresi, perioperatif eritrosit süspansiyonu transfüzyonu, komplikasyonlar ve takip süresi açısından retrospektif olarak gözden geçirildi. Ameliyat sonrası redüksiyon kalitesi ve son kontrollerdeki radyolojik sonuçlar, Matta kriterlerine göre değerlendirildi. Fonksiyonel değerlendirme için hastaların son kontrollerinde Harris Kalça Skoru, Merle d'Aubigne skoru ve Kısa Form 12 skoru uygulandı. Opere edilen taraf kalça eklem hareket açıklıkları ölçülerek kaydedildi. Bulgular: Ortalama yaş 37,4±16,3 yıl (14-69) ve ortalama takip süresi 32,6±23,9 ay (12-102) idi. Hastaların 24'ü erkek, 16'sı kadın idi. Travma oluşumundan operasyona kadar geçen süre ortalama 4,5±2,9 gündü (1-10). Yaralanma mekanizması, 22 hastada motorlu araç kazası, 14 hastada yüksekten düşme ve 4 hastada basit düşme idi. Judet-Letournel sınıflamasına göre 8 hastada anterior duvar, 8 hastada anterior kolon, 4 hastada transvers, 7 hastada anterior kolon+posterior hemitransvers, 10 hastada her iki kolon, 2 hastada transvers+posterior duvar ve 1 hastada T tipi kırık olduğu görüldü. Matta'nın redüksiyon kalitesi kriterlerine göre 30 hastada anatomik, 6 hastada kabul edilebilir ve 4 hastada kötü redüksiyon vardı. Matta'nın radyolojik evrelemesine göre radyografik sonuçlar 23 hastada mükemmel, 10 hastada iyi, 3 hastada orta, 4 hastada kötüydü. Elementer kırıklarda radyolojik evre, kompleks kırıklardan anlamlı derecede daha iyiydi. (p=0,02) Merle d'Aubigné Kalça Skoru 17 hastada mükemmel, 19 hastada iyi, 3 hastada orta ve 1 hastada kötüydü. Matta Redüksiyon Kriterlerine göre Anatomik redüksiyon sağlanan vakaların Merle D'aubigne Skoru ortalamaları, Kabul edilebilir veya Kötü redüksiyon sağlanan vakaların ortalamalarından anlamlı derecede daha yüksekti. (p=0.036) Harris Kalça Skoru 22 hastada mükemmel, 15 hastada iyi, 2 hastada orta, 1 hastada kötüydü. 2 hastada intraoperatif iliak ven yaralanması, 1 hastada postop yüzeyel enfeksiyon, 2 hastanın takiplerinde kasık fıtığı geliştiği saptandı. Sonuç: Bu çalışmanın verileri, modifiye Stoppa yaklaşımının, birçok karmaşık asetabulum kırığı için, tatmin edici radyolojik ve fonksiyonel sonuçlarla birlikte, başarılı bir yaklaşım olduğunu göstermektedir.
Objective: To evaluate the functional and radiological outcomes of acetabular fractures operated by using the Modified Stoppa approach in our clinic. Materials and Methods: Forty patients who were admitted to our clinic for acetabular fractures between 2012 and 2020, underwent surgical treatment with the Modified Stoppa approach and were followed for at least 1 year were included in this study. The records were retrospectively reviewed in terms of age, gender, type of trauma, type of fracture, accompanying injury, time to surgery, operation time, perioperative erythrocyte suspension transfusion, complications, and follow-up time. Postoperative reduction quality and radiological results at final follow-up were evaluated according to Matta criteria. Harris Hip Score, Merle d'Aubigne score and Short Form 12 score were used for functional evaluation. The hip joint range of motion of the operated side was measured and recorded. Results: The mean age was 37,4 ± 16,3 years (14-69) and the mean follow-up time was 32,6 ± 23,9 months (12-102). 24 of the patients were male and 16 were female. The mean time from trauma to operation was 4,5 ± 2,9 days (1-10). Mechanism of injury was motor vehicle accident in 22 patients, fall from height in 14 patients, and simple fall in 4 patients. According to Judet Letournel classification, 8 patients had anterior wall, 8 patients had anterior column, 4 patients had transverse, 7 patients had anterior column + posterior hemitransverse, 10 patients had associated both colon, 2 patients had transverse + posterior wall and 1 patient had T-type fractures. According to the reduction quality criteria of Matta, 30 patients had anatomical, 6 patients had imperfect and 4 patients had poor reduction. According to Matta's radiological staging, radiographic results were excellent in 23 patients, good in 10 patients, moderate in 3 patients, and poor in 4 patients. Radiological stage was significantly better in elementary fractures than in complex fractures. (p = 0.02) Merle d'Aubigné Hip Score was excellent in 17 patients, good in 19 patients, moderate in 3 patients and bad in 1 patient. According to the Matta Reduction Criteria, the mean Merle D'aubigne Score of cases with anatomical reduction was significantly higher than the mean of cases with Acceptable or Poor reduction. (p = 0.036) Harris Hip Score was excellent in 22 patients, good in 15 patients, moderate in 2 patients, and poor in 1 patient. Intraoperative iliac vein injury In 2 patients and postoperative superficial infection in 1 patient was observed. Inguinal hernia occurred in the follow-up of 2 patients. Conclusion: The data of this study show that the modified Stoppa approach is a successful approach for many complex acetabular fractures, with satisfactory radiological and functional results.